Burnout in psychological therapists: A cross‐sectional study investigating the role of supervisory relationship quality. (8th February 2020) - Johnson, Judith; Corker, Catherine; O'Connor, Daryl B.
Abstract: Background: Burnout is a growing problem in mental health‐care professionals. Clinical supervision is a mandated part of all psychological therapeutic practice but no previous study has explored whether higher quality supervision is associated with lower burnout in qualified psychological therapists. Aims: The study aimed to investigate whether the quality of the supervisory relationship was associated with two facets of burnout, exhaustion and disengagement, in a group of psychological therapists once work demands had been accounted for. Methods: Psychological therapists were recruited to complete a cross‐sectional online survey between May 2016 and January 2017. The survey measured frequency and quality of clinical supervision, workload factors, and disengagement and burnout. Data were analysed using hierarchical linear regression. Results: Two hundred and ninety‐eight qualified psychological therapists responded to the survey. Results suggested that higher quality supervision was associated with lower disengagement but not lower exhaustion. Frequency of supervision and workload variables were not associated with either facet of burnout. Female gender was associated with higher exhaustion but gender had no association with disengagement. According to previously used cut‐off scores, 235 (78.9%) participants could be classed as suffering from "high burnout, " and 173 (58.1%) participants could be classed as suffering from "high disengagement." Conclusions: There is a growing need for burnout reduction interventions in mental health‐care professionals. The present results identify a potential role for enhancing the quality of the supervisory relationship by creating more open, safe spaces for supervisees.